2011
DOI: 10.2478/v10019-011-0015-6
|View full text |Cite
|
Sign up to set email alerts
|

CD133/prominin1 is prognostic for GBM patient's survival, but inversely correlated with cysteine cathepsins' expression in glioblastoma derived spheroids

Abstract: IntroductionCD133 is a marker for a population of glioblastoma (GBM) and normal neural stem cells (NNSC). We aimed to reveal whether the migratory potential and differentiation of these stem cells is associated with CD133 expression and with cathepsin proteases (Cats).Materials and methods.The invasiveness of normal NNSC, GBM/CD133+ cell lines and GBM spheroids was evaluated in 3D collagen, as well as of U87-MG and normal astrocytes (NHA) grown in monolayers in 2D Matrigel. Expression of Cats B, L and S was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 39 publications
2
35
0
Order By: Relevance
“…The data suggested that the number of GSCs was positively correlated to the number of tumor cells, confirming the role of GSCs in tumorigenesis. Previous clinical researches have also documented that high CD133 mRNA expression in patients was a significant prognostic factor for adverse overall survival (Ardebili et al 2011;Metellus et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…The data suggested that the number of GSCs was positively correlated to the number of tumor cells, confirming the role of GSCs in tumorigenesis. Previous clinical researches have also documented that high CD133 mRNA expression in patients was a significant prognostic factor for adverse overall survival (Ardebili et al 2011;Metellus et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Main characteristics of these ten eligible studies were summarized in Table 1. The total number of patients was 715, ranging from 24 to 239 patients per study [14][15][16][17][18][19][20][21][22][23]. Nine articles were on overall survival [14][15][16][17][19][20][21][22][23], and seven studies were about progression-free survival [14-18, 21, 22].…”
Section: Study Selection and Description Of Included Studiesmentioning
confidence: 99%
“…After reviewing the abstracts, only 25 studies were preliminarily included and were further assessed by reading full text [14][15][16][17][18][19][20][21][22][23][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Fifteen studies were then excluded for other types of gliomas or the lack of usable data [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], and ten studies were finally included into the meta-analysis [14][15][16][17][18][19][20][21][22][23]. Those t...…”
Section: Study Selection and Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The importance of CD133 as a marker of tumor aggressiveness was corroborated by the correlation between CD133 expression in brain tumors and a poor clinical prognosis. [4][5][6] However, later studies revealed that CD133-negative cells can give rise to CD133-positive cells 7-9 and that both CD133-positive and CD133-negative GBM cells can initiate the development of highly aggressive tumors. 10 Moreover, diverse GCSC types -all capable of self-renewal and tumor initiation -coexist within the same GBM.…”
mentioning
confidence: 99%